2020
DOI: 10.1089/andro.2020.0006
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Intralesional Collagenase Treatment with Testosterone Therapy Provides Greater Self-Assessed Improvement in Penile Curvature due to Peyronie's Disease

Abstract: Introduction: Testosterone (T) deficiency has been reported to be associated with Peyronie's disease (PD). This study investigated response rates to intralesional injections of collagenase clostridium histolyticum (XiaflexÔ) (CCx) for penile curvature in men who simultaneously received T therapy (TTh) and in men who received CCx without TTh. Methods: Search of electronic records identified all men treated with CCx from 2013 to 2018, and whether they also received TTh during that time. Laboratory results for ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Mitsui et al 15 similarly evaluated 109 PD patients in Japan and found an inverse correlation between penile curvature and testosterone levels. 5 However, this correlation did not remain significant after adjusting for other factors. The study demonstrated that patients with severe curvature had lower mean tT levels than those with less severe curvature, but there was no significant difference between different testosterone groups or quartiles.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Mitsui et al 15 similarly evaluated 109 PD patients in Japan and found an inverse correlation between penile curvature and testosterone levels. 5 However, this correlation did not remain significant after adjusting for other factors. The study demonstrated that patients with severe curvature had lower mean tT levels than those with less severe curvature, but there was no significant difference between different testosterone groups or quartiles.…”
Section: Discussionmentioning
confidence: 86%
“…Mitsui et al 15 . similarly evaluated 109 PD patients in Japan and found an inverse correlation between penile curvature and testosterone levels 5 . However, this correlation did not remain significant after adjusting for other factors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations